Technologies in endodontic treatment of calcified channels: Case report (Research, Society and Development, 2023)
Root canals calcification can be caused by several factors such as dental trauma, physiological aging, circulatory disorders in the pulp and genetic predisposition. Given the great variability and unpredictability of endodontic treatments in calcified root canals, the level of difficulty of these therapies becomes high. In clinical practice and supported by the literature, it is possible to describe two endodontic techniques and their specificities, one in which the technology called “microsonics” is used, which involves the use of an operating microscope associated with the use of ultrasonic inserts, and the second one with the use of another technology called endoguide, which consists in using a guided access via tomography to overcome the calcification and locate the root canal. Objective: To report a clinical case in which a specific technique was used to negotiate a calcified root canal. Case description: Patient T.P.C., 50 years old, was referred for endodontic treatment of element 12, who presented clinically painful symptoms and radiographically calcification of the root canal. Computed tomography was requested, and endodontic treatment was performed in two appointments, making it necessary to use an operating microscope, ultrasonic equipment and its inserts. Conclusions: The use and association of new technological resources in endodontics, such as ultrasonic tips under magnification and guided endodontics, provides professionals with greater operational ease and safety in complex cases, thus increasing their chance of success.